Cyanobacterial bloom-associated lipopolysaccharides induce pro-inflammatory processes in keratinocytes in vitro - Raptová, P; Skočková, V; Babica, P; Sovadinová, I; Sychrová, E; Vídeňská, P; Šplíchalová, P; Vašíček, O; Šindlerová, L (Environmental toxicology and pharmacology, 2024)
Our previous studies have shown that CyanoHAB LPS (lipopolysaccharides) and LPS from cyanobacterial cultures induce pro-inflammatory effects on intestinal epithelial and immune cells in vitro. To expand our understanding, we investigated their impact on human keratinocytes, which are targeted during water recreational activities. LPS samples were isolated from CyanoHAB biomasses dominated by Microcystis, Aphanizomenon, Planktothrix, and Dolichospermum, or from axenic cultures of these genera. We identified two CyanoHAB biomasses containing a high proportion of Gram-negative bacteria, including potentially pathogenic genera. These biomasses showed the highest induction of interleukin (IL) 8, IL-6, C-C motif chemokine ligand (CCL) 2 (also known as MCP-1), and CCL20 production by HaCaT cells. Interestingly, all CyanoHAB-derived LPS and LPS from axenic cultures (except for Microcystis) accelerated cell proliferation and migration. Our findings highlight the role of G- bacteria composition and LPS structural disparities in influencing these effects, with implications for skin health during recreational activities.
Keywords: Lipopolysaccharides; Skin; Cyanobacteria; keratinocyty; Keratinocytes; Humans; jezera; sinice; lipopolysacharidy; kůže; Lakes; lidé; Microcystis